2019
DOI: 10.1021/acs.jpclett.9b01372
|View full text |Cite
|
Sign up to set email alerts
|

Proton Isomers Rationalize the High- and Low-Spin Forms of the S2 State Intermediate in the Water-Oxidizing Reaction of Photosystem II

Abstract: A new paradigm for the high- and low-spin forms of the S2 state of nature’s water-oxidizing complex in Photosystem II is found. Broken symmetry density functional theory calculations combined with Heisenberg–Dirac–van Vleck spin ladder calculations show that an open cubane form of the water-oxidizing complex changes from a low-spin, S = 1/2, to a high-spin, S = 5/2, form on protonation of the bridging O4 oxo. We show that such models are fully compatible with structural determinations of the S2 state by X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 33 publications
6
72
2
Order By: Relevance
“…We, however, note that we may not be able to detect such species, if 1) it is formed and decays before our first time point (50 μs), 2) it is short-lived due to fast formation and decay kinetics, or 3) its fraction is for other reasons 10% or less at each time point. Recent theoretical studies have shown that both forms of the S 2 state structure, the high-and low-spin forms, can be rationalized by an open-cubane structure (37,55).…”
Section: Significancementioning
confidence: 99%
“…We, however, note that we may not be able to detect such species, if 1) it is formed and decays before our first time point (50 μs), 2) it is short-lived due to fast formation and decay kinetics, or 3) its fraction is for other reasons 10% or less at each time point. Recent theoretical studies have shown that both forms of the S 2 state structure, the high-and low-spin forms, can be rationalized by an open-cubane structure (37,55).…”
Section: Significancementioning
confidence: 99%
“…Narzi et al suggested that the conversion between these two conformations could be crucial for the function of the OEC [71]. On the contrary, Corry and O'Malley suggested that the high-spin (g  4) and low spin (g = 2) EPR signals could be raised from the same conformation of the OEC, but have different protonation states of O4 (i.e., 2-O 2-or 2-OH -) in the Mn4CaO5-cluster [125]. Pushkar et al recently proposed that the high spin (g = 4) EPR signal could be raised from the early binding of the substrate oxygen to the five-coordinate Mn1 ion in the S2 state [128].…”
Section: Closer Mimicking Of the Oecmentioning
confidence: 99%
“…The origin of the g = 2 and g ≈ 4 EPR signals in both natural and artificial Mn 4 Ca-clusters have been theoretically investigated recently [71,72,100,120,[124][125][126][127][128]. It was suggested that the two EPR signals could be raised from two different conformations of the OEC in the S 2 state [72,120,125], and the g = 2 EPR signal could correspond to the structure with an open Mn 3 CaO 4 cubane, while the g ≈ 4 EPR signal may be raised with a closed Mn 3 CaO 4 cubane. Narzi et al suggested that the conversion between these two conformations could be crucial for the function of the OEC [71].…”
Section: Closer Mimicking Of the Oecmentioning
confidence: 99%
“…39 In absence of a crystal structure for the S HS 2 state, the S B 2 , S API 2 and S AW 2 structures have been proposed to give rise to the g = 4 signal, where W indicates that an additional hydroxide is bound to the Mn 4 Ca cluster, and PI signifies a proton isomer (Scheme 1). [27][28][29][30][40][41][42][43] Among these, the closed cubane S B 2 state is the most prevalent suggestion for the S HS 2 state. The S B 2 state may be reached from the open cubane S A 2 state by moving the central O5 bridge away from Mn4 so that it instead forms a bond with Mn1.…”
Section: Introductionmentioning
confidence: 99%
“…47,48 It was recently argued that the S B 2 state also does not provide a rational for many of the treatments leading to the S HS 2 state formation. 42 The latter study instead proposes a proton isomer of the S A 2 state as S HS 2 state (S API 2 in Scheme 1).…”
Section: Introductionmentioning
confidence: 99%